2022
DOI: 10.1007/s00500-022-06890-7
|View full text |Cite
|
Sign up to set email alerts
|

An autism spectrum disorder adaptive identification based on the Elimination of brain connections: a proof of long-range underconnectivity

Abstract: Autism spectrum disorder (ASD) is theoretically characterized by alterations in functional connectivity between brain regions. Many works presented approaches to determine informative patterns that help to predict autism from typical development. However, most of the proposed pipelines are not specifically designed for the autism problem, i.e they do not corroborate with autism theories about functional connectivity. In this paper, we propose a framework that takes into account the properties of local connecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Image processing-based automated software tools have been used extensively for diagnosing diseases like Alzheimer's disease [1], autism spectrum disorder [2], Schizophrenia [3], multiple sclerosis [4], brain tumours [5], from magnetic resonance (MR) images. Low contrast is one of the key issues that adversely affects the performance of software tools used for the automated analysis of MR images [6].…”
Section: Introduction 11 Background and Research Problemmentioning
confidence: 99%
“…Image processing-based automated software tools have been used extensively for diagnosing diseases like Alzheimer's disease [1], autism spectrum disorder [2], Schizophrenia [3], multiple sclerosis [4], brain tumours [5], from magnetic resonance (MR) images. Low contrast is one of the key issues that adversely affects the performance of software tools used for the automated analysis of MR images [6].…”
Section: Introduction 11 Background and Research Problemmentioning
confidence: 99%
“…[3] compared the effects of the presence and absence of long-distance transmission modes on information transmission in whole brain model, and concluded that the presence of long-distance transmission not only improves the brain's sensitivity to information but also reduces the error of information transmission. By analyzing fMRI data, [4] theorized that individual a yan-fang@sjtu.edu.cn b jiejiren@sjtu.edu.cn c zfshao@sjtu.edu.cn d *XL3A@sjtu.edu.cn differences between people may come from long-distance transmission across brain regions; [5] found that people with autism lack long-distance functional connections between brain regions. Modern anatomy has proved that myelinated axons are the material basis for information transmission between brain regions [6].…”
Section: Introductionmentioning
confidence: 99%